1998
DOI: 10.1136/oem.55.3.172
|View full text |Cite
|
Sign up to set email alerts
|

Epicondylitis among cooks in nursery schools.

Abstract: Objectives-To investigate the prevalence and risk factors of epicondylitis among cooks in nursery schools in a cross sectional study because they are suspected to have strenuous workloads on the hands and arms. Methods-Prevalence of epicondylitis among 209 nursery school cooks and 366 control workers aged 40-59 were studied. Both groups consisted of women workers chosen from 1299 subjects who agreed to participate from 1329 social welfare employees in a city. All workers were interviewed with a questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
4
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 29 publications
4
94
4
3
Order By: Relevance
“…In particular, high physical exertion and elbow movements were specifically considered as a combination because these factors have been identified in previous cross-sectional studies (10,14,16,17) and interactions between similar factors have been previously reported (10,16,17). Associations have also been previously reported with repetitive actions (12,15,16,25). Social support was a factor of interest, as the association between this factor and lateral epicondylitis has been previously reported (10,17).…”
Section: Risk Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, high physical exertion and elbow movements were specifically considered as a combination because these factors have been identified in previous cross-sectional studies (10,14,16,17) and interactions between similar factors have been previously reported (10,16,17). Associations have also been previously reported with repetitive actions (12,15,16,25). Social support was a factor of interest, as the association between this factor and lateral epicondylitis has been previously reported (10,17).…”
Section: Risk Factorsmentioning
confidence: 95%
“…The associations between occupational physical factors and prevalence of lateral epicondylitis have been clearly established, as many studies have demonstrated associations with physically forceful occupational activities (10)(11)(12)(13)(14)(15)(16)(17)(18), especially high force combined with high repetition (15,16), awkward posture (17,18) and high physical exertion combined with specific elbow movements (10). Several psychological (depression) and psychosocial (job strain, social support) work factors have also been reported to influence lateral epicondylitis (7,14,17).…”
mentioning
confidence: 99%
“…Our question addressing the patients' subjective opinions about the cause of their tennis elbow suggests that sport and occupation are among the factors that are perceived to be linked with the onset of the condition, as indeed the epidemiologic literature suggests (8)(9)(10)(11)(19)(20)(21)(22). In our study, 7% of the participants thought that their elbow problem was a direct result of playing sport, and 19% of the workers attributed their condition directly to their occupation in their baseline assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that lateral epicondylitis can be mechanically induced (7), and it has been reported to be an occupational risk for workers exposed to significant upper-limb stress (8)(9)(10)(11). For example, a study among gas and waterworks employees in Germany found that high exposure to strenuous work resulted in a 1.7-fold increase in the risk of developing the disorder (10).…”
mentioning
confidence: 99%
“…1 There is no clear association between sex and epicondylitis 3,5,6 ; however, a few studies report a higher risk in women. 7,8 Despite the fact that it is often referred to as tennis elbow, this condition occurs more commonly in nonathletes. 9 Lateral epicondylitis is clinically defined by pain at the origin of the common extensor tendon on the lateral epicondyle of the humerus with maximal tenderness usually 2 to 5 mm distal and anterior to the midpoint of the proximal muscular insertions.…”
Section: Introductionmentioning
confidence: 99%